Bahasa Inggris - Widyatmike Gede Mulawarman; Siti Halimah; Hasbi Sjamsir; Andi Aslindah; Muhammad Ibnu Sa'ad (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2026)
Early Childhood Education (PAUD) is a fundamental phase in shaping children’s character, as well as their social, emotional, and cognitive abilities. To ensure optimal child growth and development, PAUD services need to be implemented in an integrated manner through a Holistic Integrative approach (PAUD HI), encompassing education, health, nutrition, parenting, and child protection. This study aims to analyze effective multi-sector partnership strategies in the quality planning of Holistic Integrative PAUD in Samarinda City. This research employed a qualitative approach with a case study design conducted in two PAUD institutions: TK Negeri 1 Pembina and TK Islam Silmi Samarinda. The research informants consisted of school principals, teachers, representatives from technical agencies (education, health, and child protection), school committees, and parents, selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The results showed that cross-sector partnership patterns in Samarinda City have been established but remain partial. TK Negeri 1 Pembina implements a formal partnership model based on regulations and institutional frameworks, while TK Islam Silmi emphasizes a cultural approach grounded in community participation. Each model has its strengths and weaknesses: public institutions excel in accountability and documentation, whereas private institutions stand out in flexibility and social closeness. The main challenges of partnership include weak inter-agency coordination, limited resources, differing partner perceptions, and the lack of a sustainable evaluation system. With the implementation of a comprehensive partnership strategy, cross-sector collaboration has the potential to become a strategic instrument in realizing quality, inclusive, and sustainable Holistic Integrative Early Childhood Education in Samarinda City